Factors associated with type‐specific persistence of high‐risk human papillomavirus infection: A population‐based study. Issue 2 (13th August 2015) - Stensen, Signe; Kjaer, Susanne K.; Jensen, Signe M.; Frederiksen, Kirsten; Junge, Jette; Iftner, Thomas; Munk, Christian
Abstract : Persistent genital infection with high‐risk (HR) human papillomavirus (HPV) is a prerequisite for cervical cancer development. The aim of this study was to identify factors associated with type‐specific persistence of HR HPV infections. From a population‐based cohort of 40, 399 women participating in cervical cancer screening established during 2002–2005, we selected all HR HPV‐positive women ( N = 7, 778). During follow‐up (2005–2008), we collected cervical samples from these women and tested them for HPV DNA to determine type‐specific HR HPV persistence in the interval 1–4.5 years after enrolment. Data on hospitalisations, prescriptions and socioeconomic factors were obtained from nationwide registers. Women with abnormal cytology at baseline or who had undergone conisation during follow‐up were excluded. Factors associated with persistence were identified by logistic regression analysis. The overall rate of HR HPV persistence was 31.4%. The risk for persistence was significantly increased among women with a previous episode of genital warts (OR, 1.35; 95% CI, 1.04–1.74), current use of oral contraceptives (OR, 1.35; 95% CI, 1.13–1.63) or use of systemic glucocorticoids (OR, 2.04; 95% CI, 1.16–3.56). The number of pregnancies or births or use of a hormonal intrauterine device, hormonal therapy or nonsteroidal anti‐inflammatory drugs was not associated with risk for HR HPV persistence. A history of genital warts and current use of oral contraceptives or systemic glucocorticoids increased the risk, potentially indicating a decreased immune response to HPV infection. These findings suggest that host immune response characteristics are important in HR HPV persistence and consequently in cervical cancer development. Abstract : What's new? As persistent genital infection with HR human papillomavirus (HPV) is a prerequisite for cervical cancer development, it is important to increase knowledge about the factors associated with persistence of HR HPV infections. Here, the authors report a significantly increased risk for type‐specific persistence of HR HPV genital infections among women with previous episodes of genital warts and current users of oral contraceptives or systemic glucocorticoids. This large population‐based study provides support for the theory that immunological factors are important in the persistence of HR HPV infections, shedding light on the natural history of HPV and, ultimately, cervical cancer development.